The growth of the firm in (and out of) emerging economies - Peng, Mike; Lebedev, S.; Vlas, C.; Wang, J.; Shay, J. (Springer New York LLC, 2018)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature. Starting with Peng and Heath (Academy of Management Review, 21: 492–528, 1996), the growth of the firm in emerging economies (EE) has received increasing attention in the literature in the last two decades. This line of research has not only extended our knowledge on firms’ strategic choices to the context of EE, but also proposed new perspectives on the growth of the firm. Leveraging prior research, this article focuses on three major modes for firm growth—organic, acquisitive, and network-based. For each mode, we identify new themes and insights emerging from the last two decades of research. They center on (1) compositional capabilities and frugal innovations for organic growth, (2) business groups and cross-border acquisitions for acquisitive growth, and (3) network capitalism and institutional transitions for network-based growth. Overall, we not only identify new themes and insights, but also outline important yet unresolved debates as future research directions.